Adaptive piston correction of sparse aperture systems with stochastic parallel gradient descent algorithm - Xie, Zongliang; Ma, Haotong; He, Xiaojun; Qi, Bo; Ren, Ge; Dong, Li; Tan, Yufeng (Optics express, 2018)
A phased sparse aperture system provides an economic solution to get high resolution images with less volume and weight. The crucial point of such systems is adaptive correction of piston, that is, a close-loop control aiming at stabilizing the optical path differences within a fraction of the wavelength. In this paper, we present an autonomous phasing approach using stochastic parallel gradient descent algorithm through optimization of image quality. The synthetic system can be phased by iteratively commanding piston actuators without any additional optics. Simulations are first performed to test the validity. Then experimental results based on a binocular telescope testbed are presented, showing that our proposed close-loop control of piston correction doesn't only work with both laser and white-light point sources, but also with an extended object.